A solid xantphos macroligand based on porous organic polymers for the catalytic hydrogenation of CO2 - Nisters, Arne; Gutmann, Torsten; Kim, Sun-Myung; Hofmann, Jan Philipp; Rose, Marcus (RSC Sustainability)
Porous organic polymers enable a novel approach to incorporate xantphos into a solid macroligand. Immobilizing a ruthenium complex on the xantphos framework results in an excellent catalyst for the hydrogenation of CO2 to formic acid. Recycling experiments indicate a minor partial degradation of the heterogenous catalyst after a certain induction period, which is referred to its structural changes.

Highly productive V/Zn-SiO2 catalysts for the selective oxidation of methane - Kunkel, Benny; Seeburg, Dominik; Kabelitz, Anke; Witte, Steffen; Gutmann, Torsten; Breitzke, Hergen; Buntkowsky, Gerd; Buzanich, Ana Guilherme; Wohlrab, Sebastian (Catalysis Today)
The production of formaldehyde on industrial scale requires huge amounts of energy due to the involvement of reforming processes in combination with the demand in the megaton scale. Hence, a direct route for the transformation of (bio)methane to formaldehyde would decrease costs and puts less pressure on the environment. Herein, we report on the use of zinc modified silicas as possible support materials for vanadium catalysts and the resulting consequences for the performance in the selective oxidation of methane to formaldehyde. After optimization of the Zn content and reaction conditions, a remarkably high space-time yield of 12.4 kgCH2O·kgcat−1·h−1 was achieved. As a result of the extensive characterization by means of UV–vis, Raman, XANES and NMR spectroscopy it was found that vanadium is in the vicinity of highly dispersed zinc atoms which promote the formation of active vanadium species as supposed by theoretical calculations. This work presents a further step of catalyst development towards direct industrial methane conversion which may help to overcome current limitations in the future.
Keywords: Formaldehyde; Local coordination; SBA-15; Vanadium oxo species; XANES; Zinc doped silica

Mechanochemical Cyclotrimerization: A Versatile Tool to Covalent Organic Frameworks with Tunable Stacking Mode - Hutsch, S.; Leonard, A.; Grätz, S.; Höfler, M. V.; Gutmann, Torsten; Borchardt, L. (Angewandte Chemie-International Edition)
We introduce the first mechanochemical cyclotrimerization of nitriles, a facile strategy for synthesizing triazine-containing molecules and materials, overcoming challenges related to carbonization and solubility. Conducting this solid-state approach in a mixer ball mill with 4-Methylbenzonitrile, we synthesize Tris(4-methylphenyl)-1,3,5-triazine quantitatively in as little as 90 minutes. Just as fast, this mechanochemical method facilitates the synthesis of the covalent triazine framework CTF-1 using 1,4 Dicyanobenzene. Material characterization confirms its porous (650 m2 g-1) and crystalline nature. Adjusting the induced mechanical energy allows control over the obtained stacking conformation of the resulting CTFs - from a staggered AB arrangement to an eclipsed AA stacking conformation. Finally, a substrate scope demonstrates the versatility of this approach, successfully yielding various CTFs. This work presents, for the first time, the mechanochemical cyclotrimerization of nitriles. Utilizing Trifluoromethanesulfonic acid and a ball mill, both small molecules and large organic frameworks could be obtained. Screening the reaction of 1,4-Dicyanobenzene by various parameters, such as reaction time, frequency, or temperature, significant impacts on the porosity of the polymer and its crystallinity were revealed. image

Densities, Viscosities, and Self-Diffusion Coefficients of Octan-1-ol and Related Ether-Alcohols - Hoffmann, Markus M.; Gonzalez, Anthony A.; Huynh, Mandy T.; Miller, Kashane K.; Gutmann, Torsten; Buntkowsky, Gerd (Journal of Chemical & Engineering Data)
Density, viscosity, and self-diffusion coefficients are reported for octan-1-ol and the related ether-alcohols 2-pentoxy-ethan-1-ol, 3-butoxypropan-1-ol, 4-propoxybutan-1-ol, 5-ethoxypentan-1-ol, and 6-methoxyhexan-1-ol covering temperature ranges from 298.15 to 359.15 K. These new data reveal structure–property relationships affected by the presence and the position of the ether moiety in the molecular structure of the ether-alcohols. Compared to octan-1-ol, the presence of the ether moiety causes an increase in intermolecular hydrogen bonding interactions, resulting in higher densities. The increase in density is less pronounced for those ether-octanols that engage in intramolecular hydrogen bonding. As for the effects of the ether moiety on the dynamics, these are generally faster for the ether-alcohols compared to octan-1-ol, suggesting that hydrogen bonding between ether oxygen and hydroxy hydrogen is weaker compared to hydrogen bonding between two hydroxy groups. The activation energies obtained from an Arrhenius analysis are higher for translational motion than for momentum transfer for all alcohols. There are additional finer details across the ether alcohols for these activation barriers. These differences cancel out for the mathematical product of self-diffusion coefficient and viscosity (Dη). The effect of water impurities on the studied properties was also investigated and found to lead to small increases in densities for all alcohols. Viscosities decrease for octan-1-ol and 2-pentoxyethan-1-ol but increase for the other ether-alcohols that can engage in intramolecular hydrogen bonding. Density, viscosity, and self-diffusion coefficients are reported for octan-1-ol and the related ether-alcohols 2-pentoxy-ethan-1-ol, 3-butoxypropan-1-ol, 4-propoxybutan-1-ol, 5-ethoxypentan-1-ol, and 6-methoxyhexan-1-ol covering temperature ranges from 298.15 to 359.15 K. These new data reveal structure–property relationships affected by the presence and the position of the ether moiety in the molecular structure of the ether-alcohols. Compared to octan-1-ol, the presence of the ether moiety causes an increase in intermolecular hydrogen bonding interactions, resulting in higher densities. The increase in density is less pronounced for those ether-octanols that engage in intramolecular hydrogen bonding. As for the effects of the ether moiety on the dynamics, these are generally faster for the ether-alcohols compared to octan-1-ol, suggesting that hydrogen bonding between ether oxygen and hydroxy hydrogen is weaker compared to hydrogen bonding between two hydroxy groups. The activation energies obtained from an Arrhenius analysis are higher for translational motion than for momentum transfer for all alcohols. There are additional finer details across the ether alcohols for these activation barriers. These differences cancel out for the mathematical product of self-diffusion coefficient and viscosity (Dη). The effect of water impurities on the studied properties was also investigated and found to lead to small increases in densities for all alcohols. Viscosities decrease for octan-1-ol and 2-pentoxyethan-1-ol but increase for the other ether-alcohols that can engage in intramolecular hydrogen bonding.

DNP enhanced solid-state NMR – A powerful tool to address the surface functionalization of cellulose/paper derived materials - Höfler, Mark V.; Lins, Jonas; Seelinger, David; Pachernegg, Lukas; Schäfer, Timmy; Spirk, Stefan; Biesalski, Markus; Gutmann, Torsten (Journal of Magnetic Resonance Open)
This concept summarizes recent advances in development and application of DNP enhanced multinuclear solid-state NMR to study the molecular structure and surface functionalization of cellulose and paper-based materials. Moreover, a novel application is presented where DNP enhanced 13C and 15N solid-state NMR is used to identify structure moieties formed by cross-linking of hydroxypropyl cellulose. Given these two aspects of this concept-type of article, we thus combine both, a review on recent findings already published and unpublished recent data that complement the existing knowledge in the field of characterization of functional lignocellulosic materials by DNP enhanced solid-state NMR.
Keywords: solid-state nmr; dynamic nuclear polarization; Hydroxypropyl cellulose; Selective enhancement; Spin labelling

Biradicals based on PROXYL containing building blocks for efficient dynamic nuclear polarization in biotolerant media - Herr, Kevin; Höfler, Mark V.; Heise, Henrike; Aussenac, Fabien; Kornemann, Felix; Rosenberger, David; Brodrecht, Martin; Oliveira, Marcos; Buntkowsky, Gerd; Gutmann, Torsten (Journal of Magnetic Resonance Open)
A versatile strategy for synthesizing tailored peptide based biradicals is presented. By labeling the protected amino acid hydroxyproline with PROXYL via the OH functionality and using this building block in solid phase peptide synthesis (SPPS), the obtained peptides become polarization agents for DNP enhanced solid-state NMR in biotolerant media. To analyze the effect of the radical position on the enhancement factor, three different biradicals are synthesized. The PROXYL spin-label is inserted in a collagen inspired artificial peptide sequence by binding through the OH group of the hydroxyproline moieties at specific position in the chain. This labeling strategy is universally applicable for any hydroxyproline position in a peptide sequence since solid-phase peptide synthesis is used to insert the building block. High performance liquid chromatography (HPLC) and mass spectrometry (MS) analyses show the successful introduction of the spin label in the peptide chain and electron paramagnetic resonance (EPR) spectroscopy confirms its activity. Dynamic nuclear polarization (DNP) enhanced solid-state nuclear magnetic resonance (NMR) experiments performed on frozen aqueous glycerol-d8 solutions containing these peptide radicals show significantly higher enhancement factors of up to 45 in 1H→13C cross polarization magic angle spinning (CP MAS) experiments compared to an analogous mono-radical peptide including this building block (ε ≈ 14). Compared to commercial biradicals such as AMUPol for which enhancement factors {>} 100 have been obtained in the past and which have been optimized in their structure, the obtained enhancement up to 45 for our biradicals presents a significant progress in radical design.
Keywords: solid-state nmr; dynamic nuclear polarization; peptides; Biradicals; Spin labeling

Influence of TEMPO-oxidation on pulp fiber chemistry, morphology and mechanical paper sheet properties - Hillscher, Laura M.; Höfler, Mark V.; Gutmann, Torsten; Lux, Cassia; Clerkin, K. Uta; Schwall, Gerhard; Villforth, Klaus; Schabel, Samuel; Biesalski, Markus (Cellulose)
In this contribution, we report on the TEMPO-mediated oxidation of pulp fibers used in the general context of papermaking and for the future design of tailor-made paper in advanced applications. We focus in our studies on properties of TEMPO-oxidized pulp fibers to explain the characteristics of the paper made thereof. 13C solid-state NMR analysis reveals that in particular amorphous regions of the fibers are being chemically oxidized, while at the same time the crystalline regions of the fibers are not significantly affected. Investigation of the fiber morphology before and after oxidation shows that the fiber length is not changed, yet the fibers do exhibit an increase in width if in contact with water, which is attributed to an increase in fiber swelling. In addition, fibrillation decreases due to the oxidative removal of loosely bound fines and fibrils, rendering the surface of the resulting oxidized fibers much smoother in comparison to the original fibers. Finally, we observe that both, dry and wet tensile strengths are also higher for paper made of oxidized fibers, most likely due to cross linkable aldehyde groups formed during oxidation (i.e. hemiacetal bond formation in the sheet during thermal drying). Our results of the oxidation of paper fibers thus offer a systematic study helpful for the design of tailor-made paper useful in several applications where a fiber-modification with fiber-immobilized functional motifs is crucial, such as for example in paper-based microfluidic sensors (µPADs) or lab-on a chip-devices.

Solid-State NMR of Heterogeneous Catalysts - Haro Mares, Nadia; Logrado, Millena; Kergassner, Jan; Zhang, Bingyu; Gutmann, Torsten; Buntkowsky, Gerd (ChemCatChem)
Abstract Recent advances in solid-state nuclear magnetic resonance (NMR) spectroscopy, combined with dynamic nuclear polarization (DNP), quantum chemical DFT calculations, and gas-phase NMR spectroscopy investigating the structure and reactivity of heterogeneous catalysts are reviewed. The investigated catalysts range from classical mononuclear catalysts, like immobilized derivates of Wilkinson’s catalysts over binuclear catalysts such as the dirhodium paddlewheel catalyst to catalytic nanoparticles, employing various support materials, such as mesoporous silica gels, coordination polymers, and biomaterials such as cellulose.
Keywords: solid-state nmr; heterogeneous catalysis; dynamic nuclear polarization; Nanocatalysis; Surface-reactions

Ruelle-Taylor resonances of Anosov actions - Weich, Tobias; Guedes Bonthonneau, Yannick; Guillarmou, Colin; Hilgert, Joachim (J. Europ. Math. Soc.)

Monotonicity properties for Bernoulli percolation on layered graphs— A Markov chain approach - König, Philipp; Richthammer, Thomas (Stochastic Processes and their Applications)
A layered graph G^× is the Cartesian product of a graph G = (V, E) with the linear graph Z, e.g. Z^× is the 2D square lattice Z^2. For Bernoulli percolation with parameter p ∈ [0, 1] on G^× one intuitively would expect that P_p((o, 0) ↔ (v, n)) ≥ P_p((o, 0) ↔ (v, n + 1)) for all o, v ∈ V and n ≥ 0. This is reminiscent of the better known bunkbed conjecture. Here we introduce an approach to the above monotonicity conjecture that makes use of a Markov chain building the percolation pattern layer by layer. In case of finite G we thus can show that for some N ≥ 0 the above holds for all n ≥ N o, v ∈ V and p ∈ [0, 1]. One might hope that this Markov chain approach could be useful for other problems concerning Bernoulli percolation on layered graphs

A posteriori error estimates for parabolic partial differential equations on stationary surfaces - Kovács, Balázs; Lantelme, Michael Frederik Raúl (arXiv:2407.02101)
This paper develops and discusses a residual-based a posteriori error estimate and a space--time adaptive algorithm for solving parabolic surface partial differential equations on closed stationary surfaces. The full discretization uses the surface finite element method in space and the backward Euler method in time. The proposed error indicator bounds the error quantities globally in space from above and below, and globally in time from above and locally from below. A space--time adaptive algorithm is proposed using the derived error indicator. Numerical experiments illustrate and complement the theory.

Analyzing Fairness in Deepfake Detection With Massively Annotated Databases - Xu, Ying; Terhörst, Philipp; Pedersen, Marius; Raja, Kiran (IEEE Transactions on Technology and Society)

SLICE: Stabilized LIME for Consistent Explanations for Image Classification - Bora, Revoti Prasad; Terhörst, Philipp; Veldhuis, Raymond; Ramachandra, Raghavendra; Raja, Kiran (2024 IEEE/CVF Conference on Computer Vision and Pattern Recognition (CVPR))

Efficient Explainable Face Verification based on Similarity Score Argument Backpropagation - Huber, Marco; Luu, Anh Thi; Terhörst, Philipp; Damer, Naser (2024 IEEE/CVF Winter Conference on Applications of Computer Vision (WACV))

Explaining Face Recognition Through SHAP-Based Pixel-Level Face Image Quality Assessment - Biagi, Clara; Rethfeld, Louis; Kuijper, Arjan; Terhörst, Philipp (2023 IEEE International Joint Conference on Biometrics (IJCB))

NeuroIDBench: An open-source benchmark framework for the standardization of methodology in brainwave-based authentication research - Chaurasia, Avinash Kumar; Fallahi, Matin; Strufe, Thorsten; Terhörst, Philipp; Cabarcos, Patricia Arias (Journal of Information Security and Applications)

CoFE: Consistency-Driven Feature Elimination for eXplainable AI - Bora, Revoti Prasad; Terhörst, Philipp; Veldhuis, Raymond; Ramachandra, Raghavendra; Raja, Kiran (Lecture Notes in Computer Science)

ASPECD: Adaptable Soft-Biometric Privacy-Enhancement Using Centroid Decoding for Face Verification - Rot, Peter; Terhörst, Philipp; Peer, Peter; Štruc, Vitomir (2024 IEEE 18th International Conference on Automatic Face and Gesture Recognition (FG))

On the Trustworthiness of Face Morphing Attack Detectors - Al-Refai, Rouqaiah; Biagi, Clara; Chen, Cong; Raja, Kiran; Ramachandra, Raghavendra; Busch, Christoph; Terhörst, Philipp (2024 IEEE International Joint Conference on Biometrics (IJCB))

How does Rejecting Low-Confidence Decisions in Face Recognition Affect Fairness? - Saha, Pritilata; Sinha, Abhirup; Terhörst, Philipp (2024 12th International Workshop on Biometrics and Forensics (IWBF))